Changing trends in HPV vaccination in Japan. Issue 1 (31st December 2022) - Ujiie, Mugen; Kitano, Taito; Tsuzuki, Shinya
ABSTRACT: After the Japanese Ministry of Health, Labor and Welfare (MHLW) suspended its recommendation for the human papillomavirus (HPV) vaccine in June 2013, the rate of members of the new target population receiving of at least one of three doses of HPV vaccine declined, reaching 0.3% in 2016. Recently, however, the monthly number of vaccines delivered to healthcare facilities has significantly increased, from 878 doses over December 2016–April 2017 to 35, 396 doses over January–March 2021. This may be due to governmental efforts to convey information about the HPV vaccination to the eligible population and their caregivers, as well as local educational programs, despite ongoing suspension of the recommendation. The incidence of reported adverse events per vaccine dose has not increased since 2016. While governmental recommendation of the HPV vaccination remains essential for optimal vaccine coverage, the recent increase in the number of doses delivered to healthcare facilities is promising.